(untitled) - Snoeyink, Vernon L. (New York, 1980)
A first-level text stressing chemistry of natural and polluted water and its application to waste-water treatment. Discusses principles of chemical kinetics, dilute solution equilibria, effects of temperature and ionic strength, and thermodynamics in relation to water chemistry. Strong emphasis given to graphical procedures
Keywords: Water chemistry,Nước hóa học